2007
DOI: 10.1007/bf03166263
|View full text |Cite
|
Sign up to set email alerts
|

Multifrequency pulsed EPR studies of biologically relevant manganese(II) complexes

Abstract: Electron paramagnetic resonance studies at multiple frequencies (MF EPR) can provide detailed electronic structure descriptions of unpaired electrons in organic radicals, inorganic complexes, and metalloenzymes. Analysis of these properties aids in the assignment of the chemical environment surrounding the paramagnet and provides mechanistic insight into the chemical reactions in which these systems take part. Herein, we present results from pulsed EPR studies performed at three different frequencies (9, 31, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
93
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(98 citation statements)
references
References 111 publications
(156 reference statements)
3
93
1
1
Order By: Relevance
“…Continuous Wave EPR spectra of all the yeast strains, taken at X (9 GHz), Q (35 GHz), and W (95 GHz) bands and electron-spin echo EPR spectra at 35 GHz all show only intense signals from low molecular-weight Mn 2þ (S ¼ 5∕2) complexes, with no evidence of the broader features associated with Mn 2þ enzymes (28)(29)(30). However, we find that EPR spectroscopy is not sensitive to the speciation of Mn 2þ complexed with biologically available ligands (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Continuous Wave EPR spectra of all the yeast strains, taken at X (9 GHz), Q (35 GHz), and W (95 GHz) bands and electron-spin echo EPR spectra at 35 GHz all show only intense signals from low molecular-weight Mn 2þ (S ¼ 5∕2) complexes, with no evidence of the broader features associated with Mn 2þ enzymes (28)(29)(30). However, we find that EPR spectroscopy is not sensitive to the speciation of Mn 2þ complexed with biologically available ligands (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…60,61 Artificial electron acceptor phenyl- p -benzoquinone (PPBQ) was added from a 250 mM stock in DMSO to a final concentration of 1 mM. 13 C-labeled or natural abundance methanol was added to the final resuspension buffer to either 0.5 or 5% (v/v).…”
Section: Methodsmentioning
confidence: 99%
“…This causes mixing of spin states and multiple overlapping transitions, and consequently, the interpretation of spectra has been qualitative. High-field EPR studies on monomeric Mn II and Mn II have been reported in literature, which can give more accurate determinations of g - and D -values 1620 . We have developed a methodology for quantitative interpretation based on computer simulation of spectra, and here we demonstrate its use in the interpretation of X- and Q-band spectra for both parallel ( B 1 ‖ B ) and perpendicular ( B 1 ⊥ B ) orientations of the oscillating microwave field ( B 1 ) relative to the static field ( B ) 21 .…”
Section: Introductionmentioning
confidence: 99%